TRANSFORMASI ADMINISTRASI PENJUALAN GROSIR: IMPLEMENTASI SOP DI CV BOBOHO SELLER - Siti Mahmudah; Novitasari Romadhona (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the impact of implementing Standard Operating Procedures (SOP) in sales administration at CV Boboho Seller, a wholesale company in Surabaya. The SOP was applied to all stages of sales administration, from ordering, stock verification, and invoice creation to reporting, which were previously manual and are now integrated with the Olsera digital system. This research used a descriptive qualitative method, with data collected through observation, interviews, and documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing conducted iteratively to ensure the validity of findings. The results show that structured SOP accelerates workflows, improves recording accuracy, and reduces administrative errors. The digital technology allows each division to work efficiently and enhances customer satisfaction. These findings are relevant to other wholesale companies seeking to improve efficiency and productivity through administrative digitalization. This technology-based SOP model offers potential as a guide for other wholesalers in optimizing operations.